A novel R-matrix formalism for three-body channels - Raab Benedikt; Srdinko Thomas; Leeb Helmut (EPJ Web of Conferences, 2023)
At low incident neutron energies nuclear reaction cross sections exhibit a distinct resonance structure which cannot properly be described by (semi-)microscopic models. Usually R-matrix theory is applied which provides a suffi ciently accurate but phenomenological description of the resonance region. However, standard R-matrix theory is only suited for two-particle channels. Three- and many-particle channels which may occur in light nuclear systems even at rather low incident energies are usually treated in an approximative or effective way. In this contribution a novel R-matrix formalism for three-body channels and its application to nuclear systems will be presented. It is a generalized and significantly modified form of a proposal by W. Glöckle based on the Faddeev equations.